A mathematical modeling in applying hydraulic element method for a hydraulic buffer and its performance analysis. (15th June 2023) - Chen, Kefei; Li, Peng; Fan, C.G.; Yang, Y.R.; Yue, T.; Zhu, F.W.; Yuan, P.
Abstract: The hydraulic buffer is the key to decreasing the impact force between the control rod drive system and the fuel assembly in the case of an emergency shutdown of a pressurized water reactor (PWR). This paper proposes a new theoretical modeling method for studying a multi-hole hydraulic buffer featured by the variable number and location of flow holes. Four typical hydraulic elements are proposed, given the relative position of the buffer's spider and cup. The equations of each hydraulic element are firstly derived independently. Then the complete equations of the buffer are completed by assembling the equations of each hydraulic element. The numerical results obtained by this method show good agreement with the experiment results. In addition, the influence of several system parameters on the buffer's dynamical characteristics is explored by using energy dissipation rate efficiency and energy dissipation rate power. Highlights: A new hydraulic element method for modeling the fluid field of the variable hydraulic buffer is proposed. Bernoulli's equation is used to model the internal flow field of the hydraulic buffer. The energy dissipation rate is proposed to measure the characteristics of the buffer.